Plano de qualificação das equipes do serviço móvel de urgência no atendimento a pessoas em sofrimento psíquico - Oliveira, Emilia Regina dos Santos (Universidade do Vale do Rio dos Sinos, 2023)
From the beginning, mental health has been shorouded in prejudice, isolation and social exclusion. In antiquity, Society believed that mental ill nesses were caused by magical or demonic actions. The madmen roamed free a formo f exclusion with the developent of cities and indústria lization. The first establishments were created to receive the mentally ill, as well as all kids of mon- productive individuals who did not fit the moral standards of the time. The first asylum institutions had the purpose of withdrawing the mentally ill from their families to minimize the risk of harm to the Community. At the time, madness came to be perceived as na inability to work and is carriers considered incapable. With the advento f psychiatric reform in Brazil, substitute services were created to absorb these patients who were released from psychiatric institutions. The Psychosocial Care Network has difficulty absorbing and providing na excelente service to all users. The emergency care network was then structured and mobile emergency care service includes in its scope of activities the care of people in psychological distress. This work had as its main objective the development of a short-term professional plan focused on pre-hospital emergency management in mental health and as a secondary objective, to carry out na integrative literature review, aiming to assist in the elaboration of this proposal. This is a methodological study that included an integrative review, wich sought to identify the difficulties that the mobile emergency care service teams face in these calls. In a Search in the databases (SCIELO, BVS, LILACS and MEDLINE) 453 text were located dealing with psychic emergencies assisted by the mobile emergency care service. After applying the inclusion and exclusion criteria , 12 articles were selected to composse the presente work. As a result, the lack of training stands out as difficulties in caring for psychic suffering the lack of training and the deficiente knowledge of the teams to develop the service focused on the management of psychic suffering, which indicates the need for improvements aimed at professional training. The product resulting from this study is a plan for an improvement course, especially with regard to the contentes that need to be addressed, to assist mobile emergency service professionals in pre-hospital management of mental health emergencies. It is expected with this work to highlight the need for a space to acquire knowledge and expose fears and doubts regarding emergency care in mental health. There is still a need to intervene not Only in the scope of work, but throughout the training of these professionals, implementing continuing education on this topic.
Keywords: sofrimento psíquico; Urgência e emergência em saúde mental; Serviço de atendimento móvel de urgência; Psychic suffering; Urgency and emergenc in mental health; Emergency mobile care service; ACCNPQ::Ciências da Saúde::Enfermagem